The Financial and Fiscal Impacts - Sato, Motohiro; Boudreau, Laura (World Bank, Washington, DC, 2013)
The Great East Japan Earthquake (GEJE) occurred against the backdrop of a struggling economy and public finance system under stress, implying an exceptional fiscal cost and imposing a fiscal management challenge to the Government of Japan (GoJ). In response, the government committed to a full-scale national initiative that has evinced its ability to quickly mobilize short- term liquidity but leaves in question its reliance on debt issuance and taxation measures to finance longer-term reconstruction. This note examines the fiscal costs of the event, the financial measures taken by the GoJ to fund these expenses, and the fiscal implications of these actions. Lessons learned and recommendations for developing countries are distilled from this discussion. In the aftermath of the event, the GoJ announced a full-scale national response in which the government would support: 1) rebuilding disaster-resilient regions, 2) restoring the livelihoods of the disaster-affected population, and 3) reviving the local economy and industry. To finance this approach, the GoJ mobilized a portfolio of fiscal measures that minimized the financial burden on local governments, residents, and industry but significantly increased the financial burden of the central government, and thus, indirectly, of the current and future Japanese population and economy.